Soul of Beijing Opera, The : Theatrical Creativity and Continuity in the Changing World - Li, Ruru (Book collections on Project MUSE., 2010)
Any traditional theatre has to engage the changing world to avoid becoming a living fossil. How has Beijing opera -- a highly stylized theatre with breath-taking acrobatics and martial arts, fabulous costumes, and striking makeup -- survived into the new millennium while coping with a century of great upheavals and competition from new entertainment forms? Li Ruru's The Soul of Beijing Opera answers that question, looking at the evolution of singing and performance styles, make-up and costume, audience demands, as well as stage and street presentation modes amid tumultuous social and political changes. --Li's study follows a number of major artists' careers in mainland China and Taiwan, drawing on extensive primary print sources as well as personal interviews with performers and their cultural peers. One chapter focuses on the illustrious career of Li's own mother and how she adapted to changes in Communist ideology. In addition, she explores how performers as social beings have responded to conflicts between tradition and modernity, and between convention and innovation. Through performers' negotiation and compromises, Beijing opera has undergone constant re-examination of its inner artistic logic and adjusted to the demands of the external world. --Li Ruru is senior lecturer in the Department of East Asian Studies at the University of Leeds. She is the author of Shashibiya: Staging Shakespeare in China.